Bancada conceitual de medição de potência de motor mci pelo método strain gauge - Costa, Michel Platiny (Universidade Federal Rural do Semi-Árido, 2018)
Engine is a machine that transforms other forms of energy into mechanical energy. Among the various types of engines, the object in question will be the internal combustion engine (MCI), where the resulting pressure of the fuel / oxidizing mixture is used to drive the drive shaft. The equipment responsible for characterizing the engines is the dynamometer. It is used to measure force, and in its various configurations it is possible to analyze parameters such as power, torque and fuel consumption. The work provides for the development of a conceptual workbench that uses a friction dynamometer, which by means of the coupling of a brake will deform a rod and this deformation will be measured through a strain gauge device, which measures small deformations using the principle that the material changes its electrical resistance when it undergoes a deformation. As conclusion will be presented conceptual bench plus a methodology for conducting the tests.
Monografia
Keywords: Dinamômetro; Torque; MCI; ENGENHARIAS::ENGENHARIA MECANICA